Dietary lysolecithin enhances the value of high-lipid diet supplemented with fish stearin oil in post-juvenile largemouth bass Micropterus salmoides - Zhiyong Dong; Tianhong Ke; Ning Li; Baoping Zhang; Bo Wang; Jiaming Kang; Yu Zhang; Tong Qian; Liang Liu; Wanjie Cai; Trond Storebakken; Bo Shi; et al. (Aquaculture Reports, 2024)
The present study aimed to investigate the ameliorative effects of lysolecithin on fish stearin oil, meanwhile comparing the application of two different forms (lysolecithin powder and lysolecithin oil) and three inclusion levels (0.25, 0.75, 1.25 g kg−1) in largemouth bass. The entire study consisted of a 28-day digestibility trial and a consequent 68-day feeding experiment. Eight iso-nitrogenous (∼ 500 g kg−1) and iso-energetic (∼ 22 MJ kg−1) diets with high lipid level (∼ 170 g kg−1) were formulated to contain the same level of two different types of lysolecithin, and namely WFO (130 g kg−1 winterized fish oil), FSO (130 g kg−1 fish stearin oil), LLP (FSO + 1 g kg−1 lysolecithin powder, purity 250 g kg−1), MLP (FSO + 3 g kg−1 lysolecithin powder), HLP (FSO + 5 g kg−1 lysolecithin powder), LLO (FSO + 0.625 g kg−1 lysolecithin oil, purity 400 g kg−1), MLO (FSO + 1.875 g kg−1 lysolecithin oil) and HLO (FSO + 3.125 g kg−1 lysolecithin oil), respectively. Largemouth bass fed FSO showed lower apparent digestibility coefficients (ADCs) of nutrients (total fat, crude protein, gross energy, total amino acid, total essential amino acid) than the WFO. Without considering the lysolecithin type, medium and high doses (0.75, 1.25 g kg−1) significantly increased ADCs of nutrients compared with the 0.25 g kg−1 supplementation level. Lysolecithin oil significantly increased ADCs of nutrients than the lysolecithin powder. Thus, lysolecithin oil was chosen for 68-day feeding trial, and results showed the highest FBW, FI, WGR and SGR were recorded in diet HLO, and significantly higher than the FSO, LLO and MLO. Diet MLO significantly decreased lipid and energy in whole-body and lipid retention compared with the FSO, LLO and HLO. In addition, activity and mRNA expression of adipose triglyceride lipase significantly increased, while glycerol-3-phosphate acyltransferase 4 decreased in diet HLO.